Letramento literário na bebeteca: a importância da contação de histórias nas creches para o desenvolvimento dos bebês - Barboza, Monica de Oliveira Medeiros (Universidade Federal de São Carlos, 2020)
This course conclusion work aims to identify and understand the contributions of the bebeteca to reading and literary literacy in the development of babies in daycare centers. This is a bibliographical and documentary research that seeks to understand the readings in the daycare center, focusing on the mediation between babies, children's books and their mediators, knowing the reasons for such reading and the importance of literary literacy for babies from zero to one year and six months. With regard to this theme, I introduce the concepts of childhood and babies throughout the history of Brazil, as well as bring information about the emergence of daycare centers, pondering about some legislative advances and how they enable better baby development. Later, I reflect on the importance of reading in a day care center and how this practice influences babies' learning, reading and communication.Finally, I problematize literary literacy in bebetecas, exploring storytelling that can improve babies' first experiences with language and reading.In this sense, the research enables us to understand the importance of literary literacy since birth, starting from meaningful and respectful practices for babies, in addition to contributing to the mediating teacher and his repertoire of practices.
Literary literacy in the bebeteca: the importance of storytelling in daycare centers for the development of babies
Keywords: Letramento literário; Bebeteca; Educação infantil; Literary literacy; Bebeteca; Child education; CIENCIAS HUMANAS::EDUCACAO